Murine induced pluripotent stem cell‐derived neuroimmune cell culture models emphasize opposite immune‐effector functions of interleukin 13‐primed microglia and macrophages in terms of neuroimmune toxicity. Issue 2 (31st August 2020) - Quarta, Alessandra; Meese, Tim; Pieters, Zoë; Van Breedam, Elise; Le Blon, Debbie; Van Broeckhoven, Jana; Hendrix, Sven; Goossens, Herman; Hens, Niel; Berneman, Zwi; Van Nieuwerburgh, Filip; Ponsaerts, Peter
Abstract: Cellular models of induced pluripotent stem cell (iPSC)‐derived microglia and macrophages are an emerging toolbox to investigate neuroinflammation in vitro. We previously demonstrated that murine iPSC‐microglia and iPSC‐macrophages display phenotypical activation properties highly comparable to microglia and macrophages in vivo . Here we extended the characterization of iPSC‐microglia and iPSC‐macrophages with the analysis of their transcriptome profile. Next, these cellular models were employed to evaluate neuroimmune toxicity in vitro and to investigate the immune‐modulatory properties of interleukin 13 (IL13), a cytokine known for its ability to protect against neuroinflammation‐induced pathology by modulating microglia and macrophage activation. iPSC‐microglia and iPSC‐macrophages, in co‐culture with astrocyte‐committed neural stem cells (NSC), were (pre)treated with IL13 and stimulated with lipopolysaccharide (LPS) and interferon γ (IFNγ), to assess how IL13 modulates their inflammatory response. Additionally, the use of luciferase‐expressing NSC (Luc‐NSC) allowed real‐time monitoring of immune‐mediated neurotoxicity. Despite the known anti‐inflammatory properties of IL13, iPSC‐microglia primed with IL13 before LPS + IFNγ stimulation significantly increased NO secretion. This was associated with a marked reduction of the luminescence signal produced by Luc‐NSC. Interestingly, we observed that IL13 signaling has a divergent functional outcome in microglia as compared to macrophages, as for the latter no major alterations in NO release and Luc‐NSC viability were observed upon IL13 (pre)treatment. Finally, the striking IL13‐induced upregulation of NO secretion by microglia under pro‐inflammatory conditions was confirmed in vivo, where intracerebral delivery of IL13 increased inducible nitric oxide synthase mRNA expression. Concluding, we applied iPSC‐derived neuroimmune cell culture models to identify distinct neuroimmune (toxicity) responses of microglia and macrophages to IL13‐based immune modulation. Main points: Murine induced pluripotent stem cell (iPSC)‐microglia and iPSC‐macrophages as in vitro platform to study neuroinflammation and immune‐mediated neurotoxicity . In vitro stimulated iPSC‐microglia and iPSC‐macrophages respond differently to interleukin 13 immune modulation.